Asihan (mantra) sebagai adat budaya masyarakat Lampung Pepadun - Windo Dicky Irawan; Sumarno Sumarno; Juhardi Basri (Universitas Lampung, 2021)
This research is motivated by an interest in the asihan or mantra of the Lampung Pepadun cultural community, North Lampung Regency which functions to strengthen mental and self-confidence, expel evil spirits, treat sick people, defeat the forces of nature, and subdue one's heart. The purpose of this study is to describe the function and meaning of asihan or mantra for the culture of the people of Lampung Pepadun, North Lampung Regency. The data in this study were taken from the traditional elders of Lampung Pepadun in North Lampung district. Data were collected by observation, interview, and recording methods